👤

DAU COROANAAAAAAAAAAAAAA!!!!!!​

DAU COROANAAAAAAAAAAAAAA class=

Răspuns :

Explicație pas cu pas:

[tex] \frac{x}{3} + \frac{5 - x}{9} - \frac{x}{27} - \frac{2}{3} = \frac{1}{9} [/tex]

amplificam toate fractiile, pentru a scapa de numitor, acesta fiind 27.

[tex]9x + 3(5 - x) - x - 18 = 3[/tex]

9x+15-3x-x-18=3

9x-3x-x=-15+18+3

6x-x=3+3

5x=6

[tex]x = \frac{6}{5} [/tex]

Răspuns:

Explicație pas cu pas:

numitorul comun este 27

9x + 3(5 - x) - x - 9*2 = 3

9x + 15 - 3x - x - 18 = 3

5x - 3 = 3

5x = 3 + 3 = 6

x = 6/5